2022
DOI: 10.24018/ejbmr.2022.7.3.1405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dividend Policy, Investment Decision, Leverage, Profitability, and Firm Size on Firm Value

Abstract: This study aims to obtain empirical evidence related to the effect of dividend policy, investment decisions, leverage, profitability, and firm size on firm value. The population of this study is all manufacturing companies listed on the Indonesian stock exchange in 2015-2019 with 30 companies as samples. Determination of the sample in this study using the purposive sampling method. Hypothesis testing in this study uses panel data regression. The results showed that dividend policy does not affect firm value, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
1
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 0 publications
8
27
1
16
Order By: Relevance
“…This result contradicts the signal theory which shows that investment decisions send a positive signal to firm value. The outcomes of this study are in line with the results of research conducted by Anam & Nurhidayaini (2022) Jannah & Ariani (2022) and Bon & Hartoko (2022) which state that investment decisions have no significant effect on firm value.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result contradicts the signal theory which shows that investment decisions send a positive signal to firm value. The outcomes of this study are in line with the results of research conducted by Anam & Nurhidayaini (2022) Jannah & Ariani (2022) and Bon & Hartoko (2022) which state that investment decisions have no significant effect on firm value.…”
Section: Discussionsupporting
confidence: 90%
“…Investment decisions have been considered in accordance with the funds owned, it will provide benefits that will increase the value of the company. The results of the same study were also carried out by Sulistiyo (2021) and Bon & Hartoko (2022) which stated that the weighted average cost of capital had a significant effect on firm value.…”
Section: Effect Of Cost Of Capital On Firm Valuementioning
confidence: 76%
“…These findings are also established in the bank‐specific cases of Access Bank, First Bank, Zenith Bank, United Bank for Africa, ECObank, First City Monument Bank, Union Bank, Citi Bank, and Unity Bank. These research outcomes are in tandem with the findings of Bon and Hartoko (2022), Ojeyinka and Akinlo (2021), Inyiama and Victoria (2014), and Girardone et al (2004), which report evidence of no causality between size and firm performance. Meanwhile, it stands incongruent with the research outcomes of studies such as Ayetigbo and Okunlola (2022), Akinyemi and Adaramola (2018), Olaniyi, Olayemi, et al (2017), Bolarinwa and Obembe (2017), and Akinlo (2012b), which establish a bidirectional causal link between firm size and profitability.…”
Section: Presentation and Discussion Of Findingssupporting
confidence: 79%
“…This is different from the findings of the panel of researchers who found that investment decisions did not give a signal to firm value, such as the findings of Triani and Tarmidi (2020) that investment decisions in the property and real estate group of companies on the Indonesia Stock Exchange did not give a signal to firm value. Other findings by Komala et al (2019) and Bon and Hartoko (2022) found something similar but in the manufacturing sector companies.…”
Section: Introductionsupporting
confidence: 66%